Unboxing the process of revision between two design-based hybrid learning interventions - Petersen, Anne Kristine; Gundersen, Peter; Lindsø Andersen, Bjarke; Riis, Marianne (Proceedings of the International Conference on Networked Learning, 2024)
The paper investigates the revision process of a Design-Based Research (DBR) project, in which a hybrid continuing professional development (CPD) course for educators from three higher education institutions is developed, tested and redesigned. The course runs over two cycles and is based on a key design principle, which aims at fostering inter-institutional collaboration among participants in relation to developing, testing and evaluating new learning designs in the participants’ respective teaching practices. On the basis of semi-structured interviews with the course participants, it is discussed which aspects of the course should be revised and which design strategy to apply during the revision process. Moreover, the implications for the following intervention are discussed and the redesigned course is presented. The empirical contribution of the paper lies in the detailed unboxing of the steps taken by the research and design team in the revision process between the two cycles of the course. As such, the paper exemplifies data-informed revision processes in which the key design principle of a course is maintained, but the adaptation of it is fundamentally revised though the strategy of branching out, i.e. central aspects of the design are revised to create a new solution.